Performance Analysis of 68 W Flexible Photovoltaic Cell - Nayak, Jhilirani; Prasad Tripathy, Hara; Pattanaik, Priyabrata (International Journal of Psychosocial Rehabilitation, 2025)
To afford a good living standard for the individuals, there is a necessity to overcome the energy crisis. Therefore, renewable energy (green energy) sources are used extensively to obtain energy from natural sources like a solar and wind. Tapping of solar energy is given a maximum (but not enough) of consideration because wind power is available in most coastal areas. Due to technological upgrading, cost lessening in materials and government funding for renewable energy (green energy) based power generation, the growth and development of solar PV technology is increasing rapidly. Solar panels have been installed near the buildings to get energy from the sun. There are many types of solar cells are available. This letter introduces Thiemorphus thin film (tinny width) Flexible PV. A performance analysis is done on the panel that calculates its functionality